2019
DOI: 10.1108/afr-02-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agricultural credit on farm income under the Savanna and Transitional zones of Ghana

Abstract: Purpose The purpose of this paper is twofold: to determine the factors contributing to farm income in the Transitional and Savanna zones of Ghana and to ascertain variations between in the same and across the two locations; and to determine the impact of credit on farm income in each of the two zones and to ascertain the variation in impact of credit across the two locations. Design/methodology/approach In order to address endogeneity and sample selection bias, the authors draw from the theory of impact eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…These results are in agreement with the study by Pham Tien Thanh et al (2019), which found that microcredit is an effective development tool in the national poverty reduction strategy in Vietnam. The findings of Abdallah et al (2019) also indicated that credit access significantly increases farm income of smallholder farmers in Ghana.…”
Section: Impact Of Relaxing Credit Access Barriers On Income Of Cinnamon Farm Householdsmentioning
confidence: 89%
“…These results are in agreement with the study by Pham Tien Thanh et al (2019), which found that microcredit is an effective development tool in the national poverty reduction strategy in Vietnam. The findings of Abdallah et al (2019) also indicated that credit access significantly increases farm income of smallholder farmers in Ghana.…”
Section: Impact Of Relaxing Credit Access Barriers On Income Of Cinnamon Farm Householdsmentioning
confidence: 89%
“…Furthermore, the impact is more substantial among poor farmers than among economically better-off farmers. Abdallah et al [23] evaluate the impact of credit on the farmers of Ghana's savanna zones. They find that access to credit has a significant economic effect on agricultural households.…”
Section: Introductionmentioning
confidence: 99%
“…For example, whereas Gebru and Paul (2011) found that credit use resulted in positive changes in income in Tigray region, Tarozzi et al (2015) documented that credit use in Amhara and Oromia regions had only limited impact on improving household income. Other studies in Philippines (Karlan and Zinman, 2011) and SSA (Van Rooyen et al , 2012) found a negative effect of credit on income formation, whereas Ogundeji et al (2018) in Lesotho, Roxin et al (2010) in Sierra Leon and Abdallah et al (2019) in Ghana indicated a positive effect. The impact of credit on food security is found to be positive and significant in Nigeria (Idi et al , 2019) and Bangladesh (Islam et al , 2016).…”
Section: Introductionmentioning
confidence: 89%